Mapping hacks : tips & tools for electronic cartography - Erle, Schuyler (O'Reilly Media, 2005)
"The rise of electronic mapping and GPS devices has changed the way people use maps. Mapping Hacks celebrates these dramatic new possibilities, showing you how to combine free and low-cost tools with information available over the Web to read and create maps custom-tailored to your needs. Whether you're intrigued by the potential of GPS to add to your collection of electronic gadgets, have geographic data analysis problems to solve, or just love to read maps, Mapping Hacks will give you new ways to work with one of the oldest and most useful of geographic tools."--BOOK JACKET.